The Effectiveness of Psychoeducational Group with Symbolic Modeling and Bibliotherapy Techniques to Improve Career Decision Making Self-Efficacy of Junior High School Students - Basuki, Tentrem; Puji Sugiharto, Dwi Yuwono; Japar, Muhammad (Universitas Negeri Semarang, 2021)
Students who have high self-efficacy can design career plans and show persistent efforts. However, this efficacy is not always owned by every single student since there found many students having difficulties in making career decision. Thus, this study tried to examine the effectiveness of psychoeducational group with symbolic modelling and bibliotherapy techniques to improve the career decision making of Junior High School students. In carrying out the study, the researchers employed randomized pretest-posttest comparison group design by involving 42 students divided into three experimental groups. Students’ data were collected using career decision making self-efficacy scale. Based on Wilcoxon test results, the implementation of the psychoeducational groups with symbolic modelling technique, bibliotherapy, and the combination of both techniques were effective to improve students’ career decision making self-efficacy. In details, Kruskal wallis test showed that symbolic modelling and bibliotherapy techniques were more effective than their combination to improve the career decision making self-efficacy of SMP Negeri 6 Bogor students. According to these findings, counselors are recommended to apply symbolic modelling and bibliotherapy techniques separately to improve students’ career decision making self-efficacy